Report on the Phytoplankton Pigments measured during the JARE-32 Cruise to Syowa Station, Antarctica, November 1990 to March 1991 - Kuramochi, Toshiaki; Suzuki, Toshikazu; Fukuchi, Mitsuo (National Institute of Polar Research, 1996)
P(論文) departmental bulletin paper